The French Presence in the South Pacific, 1842–1940 - Aldrich, Robert. author. aut Link
XII, 387 p.
Keywords: An examination of France's presence in the South Pacific after the takeover of Tahiti. It places the South Pacific in the context of overall French expansion and current theories of colonialism and imperialism and evaluates the French impact on Oceania.